2010
DOI: 10.1002/ppul.21372
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of the SLC9A3 gene on susceptibility to infections and pulmonary function in children with cystic fibrosis

Abstract: In cystic fibrosis (CF), CFTR dysfunction leads to salt and water imbalance across airway epithelia, depleted surface liquid layer, and impaired mucociliary clearance. This provides optimal conditions for chronic bacterial infections leading to excessive inflammation and progressive obstructive lung disease. We hypothesized that other epithelial channels affecting salt balance across the airways may play a role in the susceptibility to bacterial infections and modulate severity of CF lung disease. The SLC9A3 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 33 publications
1
32
0
Order By: Relevance
“…Some studies looked for associations between SNPs and age at first infection of P. aeruginosa [5,29] whereas others looked for the frequency of Pa colonization. Chronic Pa colonization is age-dependent and the majority of cystic fibrosis patients become colonized over time.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies looked for associations between SNPs and age at first infection of P. aeruginosa [5,29] whereas others looked for the frequency of Pa colonization. Chronic Pa colonization is age-dependent and the majority of cystic fibrosis patients become colonized over time.…”
Section: Discussionmentioning
confidence: 98%
“…Large-scale genetic studies have indicated that genetic variants of SLC9A3 are associated with early infection, lung infection severity, and susceptibility to meconium ileus in patients with CF [2831]. However, the association between CBAVD, a mild phenotype of CF, and SLC9A3 is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms in SLC9A3 in children with CF are significantly associated with two clinical manifestations, the early infection of Pseudomonas aeruginosa and worsened pulmonary function [28]. Genome-wide association studies have indicated that genetic variants of SLC6A14 , SLC26A9 , and SLC9A3 in patients with CF ( n = 3,763) increased susceptibility to early meconium ileus [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…further supporting the hypothesis that the inhibition of the SLC9A3 transporter could ameliorate the severity of CF disease. Association analyses in young Canadian CF patients revealed the role of this transporter in the susceptibility to earlier onset of Pseudomonas infections and correlated with the decline of lung function [61]. Furthermore, in the NACGMS GWA study several markers on chromosome 5, spanning several genes including AHRR, EXOC3 and SLC9A3, showed suggestive signal, not reaching genome-wide significance, indicating that additional variants in the SLC9A3 and neighboring genes contribute to the variability of the CF lung disease.…”
Section: Gene Modifier Studies Highlight Ion Exchangers and Alternatimentioning
confidence: 93%